History of ancient copper smelting pollution during Roman and medieval times recorded in Greenland ice - Hong, Sungmin; Boutron, Claude F.; Patterson, Clair C.; Candelone, Jean-Pierre (1996)
Determination of copper concentrations in Greenland ice dated from seven millennia ago to the present showed values exceeding natural levels, beginning about 2500 years ago. This early large-scale pollution of the atmosphere of the Northern Hemisphere is attributed to emissions from the crude, highly polluting smelting technologies used for copper production during Roman and medieval times, especially in Europe and China. This study opens the way to a quantitative assessment of the history of early metal production, which was instrumental in the development of human cultures during ancient eras.